TANGGAP JUMLAH BUAH PER POHON TERHADAP HASIL DAN KUALITAS BENIH EMPAT GALUR HIBRIDA MENTIMUN (Cucumis sativus ) - Uun Sumpena (MEDIAGRO, 2014)
This experiment was done at Research Institute for Vegetable, from  January  to Juli 2013. The objective of experiment is to know the fruit number would give the best effect of production, viability and seed vigor of four cucumber lines. The experimental design was split plot  with two replications in the field and three replications in the laboratory for seed. The treatments were two factors; the first was Lines (G); Lines 1 ( G1), Lines 2  (G2), Lines 3 (G3) and Lines 4 (G4).  The second factor was fruit number per plant (t); fruit number per plant inbounded (t0) three  fruit per stem (t1) six fruit per stem (t2) and nine fruit per stem (t3). Results of the experiment sowed that the interaction between fruit number per plan which is left with four cucumber lines. Hybrid line 1 results the highest seed weight per plant, as for hybrid line 3 results the highest seed weight per 1.000 grain, although have the same weight with hybrid line 2. Between cultivars were not significant in vigor of growth and vigor of keeping. The treatment of nine fruit per plant (t3) result the best yield of four cucumber hybrid lines and seed quality was the same treatment with three fruit per plant (t1) and six fruit per plant (t2).   Keywords: Cucumber hybrid lines, fruit number, quality seed, yield